Gender and Work Hours Transitions in Australia : Drop Ceilings and Trap-Door Floors - Robert William Drago; David Black; Mark Wooden (Institute for the Study of Labor (IZA), 2004)
We introduce the ideas of ?drop ceilings?, that full-time employees who switch to reduced hours thereafter face an hours ceiling such that a return to full-time employment is difficult, and of ?trap-door floors?, that full-time employees may be denied the opportunity to reduce their hours and instead face a choice between full-time employment and quitting the job. These ideas derive from the potential existence of norms around the ideal worker and motherhood. Relevant hypotheses are developed and tested using information on usual and preferred working time from the first two waves of the Household, Income and Labour Dynamics in Australia survey. The key findings are that women face drop ceilings significantly more often than men; that professionals and managers confront trap-door floors significantly more often than employees in other occupations; and that trap-door floor effects are generally stronger than drop ceiling effects in the data.
Keywords: J22; J23; 330; working hours; employment transitions; HILDA survey; Arbeitszeitflexibilisierung; Geschlecht; Führungskräfte; Erwerbsverlauf; Schätzung; Australien